Determining the Cost of Business Continuity Management - A Case Study of IT Service Continuity Management Activity Cost Analysis - Syrjänen, Kimmo (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2022)
This single organisation case study discusses the cost of business continuity management in IT services. Information technology (IT) expenses can amount to a substantial part of operational costs in a company, and IT leaders tend to aim for thorough IT cost management to meet financial targets. Thus, information security activities such as business continuity management (BCM) rank among the most important concerns for IT leaders. Despite the concerns of IT management, senior management appears to be hesitant to spend on BCM as much as IT management would hope for. Senior management may struggle with the question of how to justify spending on an activity that proves its usefulness only when a rare event occurs. The challenge for measuring costs of sociotechnical activities was the inspiration for this work – to find out whether the cost of business continuity management (BCM) could be explained better to help decision making. Two main paradigms emerged from literature – BCM activities in the context of organisational routines, and IT cost and information security cost classifications. The theoretical assumption was that the relationship between IT costs and BCM activities emulates the activity- based costing theory (ABC) – the premise of cause-and-effect relationship between activities and costs. The key question is “How to determine the cost of BCM activities in IT services?” To find out, I used comprehensive archival data set from a case company and designed a retrospective quantitative model to analyse the association between BCM activities and IT costs. By employing causal-comparative method and multiple linear regression analysis, I compared distinct groups of IT services to determine how much of the variation in IT costs could be explained by BCM activities. In addition, I measured the relative effect of each independent variable towards the total cost of BCM. As both statistical and practical significance test results were supported, several interesting results were observed between BCM activities and IT costs – namely human, technology and organisational resources, as well as IT service designs. The research presents two theoretical contributions and one empirical contribution to the theory. The first and primary contribution is the BCM activity cost model. This is the final product for the main research question of determining the cost of BCM in IT services. The second contribution is the total cost of BCM framework. This framework contributes to the broader academic discussion of information system (IS) cost taxonomies in IT services and information security. The third contribution is empirical confirmation how to observe unknown cost effects by multiple regression analysis. Learnings from this research can contribute IS researchers focused on the economic aspects of IS and IT. The research also introduces three practical contributions. The first one considers the observation of overall BCM cost effects on IT services. Although the results of a single case study cannot be generalized directly to every organization, information herein may aid companies to evaluate BCM impact on their budgets. The second practical contribution considers the challenges regarding measurement of activity costs that can be difficult to observe directly. Within the limitations of this research, nothing here suggests that the BCM activity cost model could not be productized and integrated into other cost appraisal tools in a company or applied in other IT service management areas. The last important practical contribution are the definitions of BCM activity cost variables. Confirming the cost association between theoretical and empirical BCM frameworks can help BCM professionals to promote BCM process.

Tämä yhden organisaation tapaustutkimus pohtii jatkuvuudenhallinnan kustannusten osuutta tietojärjestelmäpalveluissa. Informaatioteknologian (IT) kustannukset saattavat muodostaa merkittävän osa yrityksen menoista, ja IT-johtajat pyrkivät yleensä tarkkaan kulujenhallintaan saavuttaakseen yrityksen taloudelliset tavoitteet. Siksi tietoturva-aktiiviteetit kuten jatkuvuudenhallinta (business continuity management, BCM) ovat heidän olennaisimpia huolenaiheitaan. IT-johtajien huolista huolimatta ylin johto ei yleensä ole kovin innokas panostamaan BCM:ään niin paljon kuin IT-johto toivoisi. Ylin johto saattaa tuskailla sen kanssa, miten perustella kulut toimiin, joita kaivataan vain harvinaisissa poikkeustilanteissa. Sosioteknisten kulujen mittaamisen haaste antoi inspiraation tälle tutkimukselle; tavoite oli selvittää, olisiko mahdollista selittää BCM-kustannuksia paremmin päätöksenteon tueksi. Kirjallisuudesta nousee esiin kaksi keskeistä aihepiiriä: BCM organisaation toimintatapojen kontekstissa sekä IT-ja tietoturvakulujen luokittelu. Teoreettinen oletus oli, että IT-kulujen ja BCM- toimenpiteiden suhde emuloi toimintolaskennan (activity-based costing, ABC) teoriaa – se, että toimenpiteiden ja kulujen välillä on syy-seuraussuhde. Avainkysymys on ”Miten määritellä BCM- toimenpiteiden kulut IT-palveluissa?” Tämän selvittämiseksi käytin kattavaa arkistodataa caseyhtiöstä ja kehitin retrospektiivisen kvantitatiivisen mallin analysoidakseni BCM-toimenpiteiden ja IT-kulujen suhdetta. Kausaalis-komparatiivisen metodin ja lineaarisen regressioanalyysin avulla vertailin erilaisia IT-palvelujen ryhmiä selvittääkseni missä määrin BCM-toimenpiteet voisivat selittää IT-kulujen vaihtelua. Lisäksi mittasin jokaisen muuttujan suhteellisen vaikutuksen BCM:n kokonaiskustannuksiin. Kun sekä tilastolliset että käytännölliset testitulokset huomioitiin, BCM- toimenpiteiden ja IT-kulujen suhteesta ilmeni useita kiinnostavia tuloksia: sekä inhimillisiä että teknologia- ja organisaatioresursseihin ja IT-palvelujen muotoiluun liittyviä. Tutkimus tuotti kaksi teoreettista kontribuutiota sekä yhden empiirisen todistuksen teorialle. Ensimmäinen ja olennaisin näistä on BCM-toimenpiteiden kustannusmalli. Tämä lopputuotos vastaa tutkielman avainkysymykseen BCM-kuluista IT-palveluissa. Toinen kontribuutio on BCM-kehyksen kokonaishinta. Tämä voi ruokkia laajempaa akateemista keskustelua tietojärjestelmien (information system, IS) kustannustaksonomioista IT- palveluissa ja tietoturvassa. Kolmas kontribuutio, empiirinen todistus, osoittaa epäsuorien kulujen mittaamisen olevan mahdollista regressioanalyysiä hyödyntäen. Tutkimuksen havainnoista voi olla hyötyä IS:n ja IT:n taloudellisiin aspekteihin keskittyneille IS-tutkijoille. Tutkimuksesta nousee esiin myös kolme käytännön kontribuutiota. Ensimmäinen liittyy siihen, miten BCM-kokonaiskulujen vaikutuksia IT-palveluihin seurataan. Vaikka yhden tapaustutkimuksen tuloksia ei voida yleistää, tutkimuksen havainnot voivat auttaa yrityksiä arvioimaan BCM:n vaikutuksia budjetteihinsa. Toinen käytännön kontribuutio liittyy haasteisiin siinä, kuinka mitata toimenpidekustannuksia, joita on hankala tarkkailla suoraan. Tämän tutkimuksen rajoissa ei ilmennyt mitään syytä sille, etteikö BCM-toimenpiteiden kustannusmallia voitaisi tuotteistaa ja integroida yrityksen muihin kustannusarviotyökaluihin tai etteikö sitä voisi soveltaa muille IT-palvelujen hallinnon alueille. Viimeinen merkittävä käytännön kontribuutio on BCM-toimenpiteiden kustannusmuuttujien määrittely. BCM-ammattilaiset voivat helpommin edistää BCM-prosessia, kun teoreettisten ja empiiristen BCM-kehysten kulujen vastaavuus vahvistetaan.